A new real–time control method for free locomotion in a walking robot. (4th August 2014) - Soto, J. Emilio Vargas
This paper presents a new real–time control method for free locomotion in a walking robot. The walking robot, named RIMHO, has been developed as an exercise in expert control of legged locomotion. A brief description of the robot and its model are given. A description of the relationship between the machine level and the control station level is presented. The paper also presents a new free locomotion method for forward and turning gaits. The locomotion method shows an interesting phrasing to solve the stability problem at the beginning of locomotion from any initial configuration of the robot. The new real–time control method is used by a human to operate the robot using a virtual reality representation in the control station machine. In this way, a three–dimensional graphical representation in real time is used to test the effectiveness of the locomotion.